FACTORS ASSOCIATED WITH UNDER NUTRITION AMONG CHILDREN 2 – 5 YEARS LIVING WITH HIV/AIDS IN BOMBO MILITARY BARRACKS, LUWERO DISTRICT CENTRAL UGANDA. A CROSS-SECTIONAL STUDY DESIGN. - Alimocan , Anna; Turumanya , Judah; Nalubega, Jane Frank (Student’s Journal of Health Research Africa, 2023)
Background: The HIV epidemic is a major public health concern and is associated with a range of long and short- term health consequences. Children living with HIV/AIDs related illnesses are still among the leading causes of infant mortality. This study sought to determine the factors associated with undernutrition among children 2 to 5yrs living with HIV in Bombo Military Barracks, Luwero District Central Uganda. Methodology: The researcher used a descriptive research design to study the study variables. A sample size of 56 participants was selected. Both primary and secondary data sources were used by the researcher. Structured questionnaires, FGDs, and interviews were conducted to collect data, and this data was sorted, edited, coded, and analyzed using SPSS, Dedoose, and WHO Anthro software. Results: The findings of the study showed that nutrition status of children is determined by socioeconomic factors and IYCF Practices. More females (60.9%) were enrolled in the study compared to males (39.3%). 6% of girls have a WFH <-3SD, 15% <-2SD, 34% <-1SD and 1% >+1SD. While, 4% of boys have a WFH <-3SD, 9% <-1SD and 26% >+1SD. Children aged between 2 – 3 years are more wasted with a Mean z-Score of -2SD compared to those aged between 4 – 5 years with a mean score of -1SD. This implies that the independent variable directly influences the independent variable. Conclusion: Data analysis has as well indicated that most of these children have been breastfed for over 12 months and hence introduced to home-cooked meals at the appropriate time. Recommendations: Ministry of health and organizations with nutrition-related programs should take into consideration providing HIV targeted nutrition education.